FACTORS RELATED TO NUTRITIONAL STATUS IN PRE-SCHOOL CHILDREN - Dwi Rahayu Candra Pertiwi; Ivon Diah Wittiarika; Atika Atika; Wahyul Anis (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: The problem of nutrition in children at Indonesia was still an unresolved problem. Unicef said that one in ten children were underweighted and a fifth of children were overweighted or obesed. This number will not decrease and it will increase if we not handled this problem seriously. This study was conducted with the aimed of analyzed the factors that influenced nutritional status in pre-school children, so that more effective prevention and treatment can be carried out. Method: This research was a cross sectional study with a total sample of 150 preschool child in the age of 3 to 6 years old and the parents with online questionnaire. Sampling was done by cluster random sampling. The study was conducted in PAUD at Tanah Kali Kedinding, Kenjeran, Surabaya. The data was analyzed with Spearmean test, Chi-square, and Fisher exact. Result: Knowledge p value = 0,025 r = 0,182. Income p value < 0,001 r = 0,368. Eating frequency p value < 0,001 r = 0,721. The amount of food p value < 0,001 r = 0,738. The kind of food p value < 0,001 C = 0,443. Physical activity p value = 0,438. Conclusion: Parental knowledge and income, and children's eating patterns were related to the nutritional status of pre-school children, while the physical activity of children does not affected the nutritional status of children.